Socio-economic inequality of chronic non-communicable diseases in Bangladesh - Biswas, Tuhin; Islam, Md Saimul; Linton, Natalie; Rawal, Lal Bahadur (© 2016 Public Library of Science, 2018)
This article was published in the PLoS ONE [© 2016 Biswas et al.] and the definitive version is available at: http://doi.org/10.1371/journal.pone.0167140 The Journal's website is at: http://journals.plos.org/plosone/article?id=10.1371/journal.pone.0167140